2018
DOI: 10.1101/310029
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The landscape of selection in 551 Esophageal Adenocarcinomas defines genomic biomarkers for the clinic

Abstract: 14Esophageal Adenocarcinoma (EAC) is a poor prognosis cancer type with rapidly rising incidence. Our 15 understanding of genetic events which drive EAC development is limited and there are few molecular 16 biomarkers for prognostication or therapeutics. We have accumulated a cohort of 551 genomically 17 characterised EACs (73% WGS and 27% WES) with clinical annotation and matched RNA-seq. Using a 18 variety of driver gene detection methods we discover 65 EAC drivers (66% novel) and describe 19 mutation and CNV… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
128
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(139 citation statements)
references
References 62 publications
11
128
0
Order By: Relevance
“…The amplified genes can be grouped into functional biological pathways with the RAS-ERK signalling pathway (e.g. ERBB2; EGFR; KRAS) and GATA transcription factors (GATA4; GATA6) being the most common (Frankell et al, 2019; Lin et al, 2012; The Cancer Genome Atlas Research Network et al, 2017). The morphology of BO differs from the oesophageal epithelia by the presence of a columnar epithelium and secretory goblet cells, rather than squamous epithelium (reviewed in Spechler and Souza, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The amplified genes can be grouped into functional biological pathways with the RAS-ERK signalling pathway (e.g. ERBB2; EGFR; KRAS) and GATA transcription factors (GATA4; GATA6) being the most common (Frankell et al, 2019; Lin et al, 2012; The Cancer Genome Atlas Research Network et al, 2017). The morphology of BO differs from the oesophageal epithelia by the presence of a columnar epithelium and secretory goblet cells, rather than squamous epithelium (reviewed in Spechler and Souza, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…1E, Table S1 (A companion study investigating Barrett's esophagus WGS dataset in detail is currently in preparation). In summary, our analysis included 1,668 WGS samples not currently within the Pan-Cancer Analysis of Whole Genomes (PCAWG) effort, including published studies (Nik-Zainal et al, 2016;Hayward et al, 2017;Baca et al, 2013;Barretina et al, 2012;Frankell et al, 2019), The Cancer Genome Atlas (TCGA, 1017 cases), International Cancer Genome Consortium (ICGC, 876 cases), or Cancer Cell Line Encyclopedia (CCLE, 326 cases) (Barretina et al, 2012;Ghandi et al, 2019). Though the majority of our analyzed samples consisted of primary tumors, 283 out of the 2,833 samples were extracted or derived from metastatic tumors.…”
Section: Introductionmentioning
confidence: 99%
“…One reason for the poor prognosis is the lack of tailored therapies due to the relative paucity of molecular knowledge compared to other cancers. We are beginning to understand the molecular mechanisms underpinning this disease, chiefly through genomic sequencing studies, which have revealed multiple genes that are recurrently mutated in OAC (Dulak et al 2013;Weaver et al, 2014;Ross-Innes et al, 2015;Frankell et al, 2018). However, with the exception of TP53, the overall incidence of mutations in individual genes is low.…”
Section: Introductionmentioning
confidence: 99%